Peningkatan Kemampuan Siswa Dalam Memecahkan Masalah Matematika Bentuk Cerita Melalui Pendekatan Scientific Terintegrasi Pada Problem Based Learning (PBL) (PTK Pada Siswa Kelas VIIE Semester Genap di SMP Negeri 2 Sawit TahunAjaran 2014/2015) - Susanto, Budi; , Dra. Sri Sutarni, M.Pd (2015)
The purpose of this study was to determine the increase in mathematical problem based learning in mathematics learning story form with an integrated approach Scientific at the Problem Based Learning in VIIE grade students of SMP Negeri 2 Sawit academic year 2014/2015. Students as the recipient amounting to 29 students. research actions performed by using research methods class action consisting of two cycles, where in the first and second cycle each consisting of two meetings. Data collection methods used in this study include observation, field notes, and documentation. Data analysis techniques performed by the method of flow, which is the process of data analysis, data presentation, and verification data. research result showed an increase in mathematical problem based learning is reflected mathematics. that matter several indicators as follows: (1) Understanding the problem as much as 10 people (34,48%), (2) Planning for completion by 9 people (31.03%), (3) Running a plan of 8 people (27.58%), (4) Looking back at what has been done by 7 people (24,14%) The results of the above description is concluded that the implementation of an integrated approach at the Scientific Problem Based Learning can improve the shape of mathematical problem solving in mathematics learning stories on VIIE grade students of SMP Negeri 2 Sawit academic year 2014/2015.